THE INFLUENCE OF LAND SUBSIDENCE TO THE CHANGES OF INUNDATION WIDTH IN SEMARANG CITY ALLUVIAL PLAINS (Case Study: Northern Districts of Semarang) - Pratikso Pratikso; Soedarsono Soedarsono; Eky Sulistiyo Hariawan (International Conference on Coastal and Delta Areas, 2017)
Semarang city is geographically consisting two units of morphology, namely: in the southern part is a denudasional structural hills consisting of Tembalang, Tanah Putih, Tegalsari, Siranda, until Gajah Mungkur. While the alluvial plain lies in the northern part. Land subsidence in some parts of Semarang city becomes a serious problem, because the area is generally a settlement area. As a result of land subsidence, settlement areabecomes lower, because the settlement location partly close to the beach, during a tide it overflows into the mainland through rivers and drainage canals and then it pooled to the settlement. The purpose and goal of this study is to assess and predict the large and length of land subsidence on alluvial plain due to the load and the mechanical properties of the soil as well as to assess and predict the changes of the inundation width in the alluvial as a result of land subsidence. This research use experimental method. To test the analysis of alluvial sediment subsidence, it is obtained by the calculation based on samples and primary data in the laboratory. The calculation is done in two ways, the first way is calculating the physical model with 1D Terzaghi, while the second way is predicting the subsidence using PLAXIS software and the result is the prediction of the large and length of subsidence with load variations and different soil mechanical conditions. Furthermore, comparing the calculation result using a physical model with the calculation result using PLAXIS software to get the final result of how is the large and length of land subsidence and the tendency of the subsidence. Whereas to calculate the width of the inundation, it is planned the changes of the inundation width using GIS software (Geographic Information System). The result of this study which applies 1D Terzaghi approach, obtained the smallest subsidence is 64,2 cm for 17,781 years and the largest subsidence is 107.600 cm for 29,635 years. While the approach which applies PLAXIS software obtained the smallest subsidence is 65.8 cm for 17,781 years and the largest subsidence is 110,000 cm for 29,635 years. The subsidence tendency more northern is larger and the time is longer. Land subsidence in the alluvial plain continues to rise, therefore the inundation in the settlement that located close to the river and the beach continues to grow wider, between 2016 and 2045 there is additionalinundation of 493,63 Ha. Keywords: Alluvial, Subsidence, Inundation, GIS, PLAXIS